Unusual Variant of Coronal Bladder Duplication Associated with Glans Diphallia: A Case Report and Review of the Literature - Reza Khorramirouz; Amin Bagheri; Abdol-Mohammad Kajbafzadeh (Case Reports in Urology)
Bladder duplication is a rare congenital anomaly which occurs in the sagittal or coronal plane and it can be associated with other anomalies. It has been previously classified as complete duplication of the bladder and urethra or incomplete duplication with two bladders and common urethra. However, complete duplication of bladder with a single urethra has been rarely reported. Herein, we present a patient with a different variation of bladder duplication in the coronal plane with two urethras originating from the main bladder and associated glans diphallia.